Clinical Study on the Combined Application of Ultrasound Probes to Improve the Diagnostic Value of Adenomyosis at the Bottom of the Gallbladder - Ma HY; Wu T; Yin GM; Ma YH; Wang Q; Zhao XY; Lu YY (Journal of Multidisciplinary Healthcare)
Hong-Ying Ma,1 Tao Wu,1 Guo-Mei Yin,1 Ya-Hui Ma,1 Qing Wang,1 Xiao-Yu Zhao,2 Yi-Yan Lu3 1Department of Ultrasound, Aerospace Center Hospital, Beijing, 100049, People’s Republic of China; 2Department of Ultrasound, Yixian Hospital of Traditional Chinese Medicine, Baoding, 074200, People’s Republic of China; 3Department of Pathology, Aerospace Center Hospital, Beijing, 100049, People’s Republic of ChinaCorrespondence: Yi-Yan Lu, Department of Pathology, Aerospace Center Hospital, No. 15 Yuquan Road, Haidian District, Beijing, 100049, People’s Republic of China, Tel +86 18910272558, Email yiyanluu@126.comObjective: This study aims to assess the diagnostic efficacy of using a combination of ultrasonic probes including convex array probe, linear array probe, and intracavitary probe, for the detection of adenomyosis at the gallbladder fundus.Methods: A total of 121 outpatients with suspected diagnosis of gallbladder adenomyosis were enrolled in this study. All patients underwent conventional ultrasound examination of gallbladder floor with convex array probe, linear array probe and intraluminal probe. The thickness, length and internal echo characteristics of the lesions were recorded in detail.Results: The mean size of adenomyosis at the gallbladder fundus was found to be 1.177 ± 0.775 cm across the 121 individuals studied. The convex array probe successfully detected adenomyosis in 87 cases, while 34 cases returned negative results. The combined probes identified adenomyosis in 102 cases, with 19 cases yielding negative results. Both types of probes were concordantly positive in 77 cases and concordantly negative in 9 cases (P = 0.018).Conclusion: The combined use of different ultrasonic scanning probes—convex array probe, linear array probe, and intracavitary probe—significantly enhances the diagnostic accuracy for adenomyosis at the gallbladder fundus, demonstrating significant clinical utility.Keywords: adenomyosis, combined application of ultrasonic probe, convex array probe, intracavitary probe, linear array probe, gallbladder fundus